Stroke as Sequel to Varicella Vaccination - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Two children, ages 18 months and 14 months, who presented with acute hemiparesis 5 days and 3 weeks following varicella vaccination are reported from Alberta Children's Hospital, and the University of Calgary, Ontario, Canada.